Non-communicable Diseases and Oral Health: An Overview - Wolf, Thomas Gerhard; Cagetti, Maria Grazia; Fisher, Julian-Marcus; Seeberger, Gerhard Konrad; Campus, Guglielmo (Frontiers in Oral Health, 2021)
Non-communicable diseases (NCDs) such as cardiovascular and metabolic diseases, diabetes, cancer and diseases of the oral cavity such as caries or periodontitis represent a global and highly relevant problem due to demographic and epidemiological changes. NCDs are not only responsible for millions of deaths worldwide, but they cause relevant costs for national economies arise for the health care of societies. Assuming that oral health and general health are directly linked, emerging interactions between systemic and oral diseases are increasingly being researched. Common important risk factors have implications for economic, social, and moral determinants of health. Interdisciplinarity trained oral health professionals are needed to address the excessively high rates of inequities in oral health. The main reason that oral diseases are still a global health problem is related to mainly individual subjective high-risk approaches, which resulting in high costs and low effectiveness. A paradigm shift for a public health approach is needed at population level that integrates different health professionals who deal with NCDs. Oral care, like physical activity, is one of the most important lifestyle-related determinants of health. Widespread recognition of this kind of approach is critical to both reducing the impact of oral and non-oral NCDs. A multi-sectoral, comprehensive and integrated strategy is therefore necessary. The focus should be on social, environmental and population strategies, but should also support individual strategies.